The Architecture of Management Accounting Systems Change: A Multidimensional Approach - WILLIAMS, John Joseph (Institutional Knowledge at Singapore Management University, 2003)
We extend the model developed by Williams and Seaman [Williams, J. J. & Seaman, A. E. (2001). Predicting change in management accounting systems: national culture and industry effects. Accounting, Organizations and Society, 26, 443–460] and utilize the same sample of 93 Chinese family owned businesses to test the multivariate relationship between a set of operational effectiveness measures and a set of changes in management accounting and control systems components under the contingency effects of size, organizational capacity, intensity of competition and centralization. Significant relationships emerge for high intensity of competition, high centralization, and low and high levels of organizational capacity. Variables of major importance in these relationships converge to form two larger patterns of a structural and environmental nature, which are consonant with the core national cultural values of Singapore documented in the contemporary cross-cultural management control literature.